Drumming and digital inclusion: music, identity formation, and transformative empowerment in Afro-Brazilian community development NGOs. Issue 3 (3rd April 2018) - Straubhaar, Joe; Davis, Stuart
ABSTRACT: This article draws upon music training programmes developed by Afro-Brazilian activists in the city of Salvador, Bahia, as a strategy for connecting training in musical production with computer skills. Though a seemingly incongruous pairing, we argue that for Afro-Brazilian young people learning how to create music helps provide a sense of cultural identity and consciousness that helps them then move into learning about technology. This two-step process creates a sense of "transformative empowerment" where a transformation in individuals' sense of cultural identity facilitates changes in more professionalised areas addressed through the discourse on information and communications technologies for development (ICT4D).